2013
DOI: 10.1016/j.bbamcr.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear respiratory factor 2 regulates the expression of the same NMDA receptor subunit genes as NRF-1: Both factors act by a concurrent and parallel mechanism to couple energy metabolism and synaptic transmission

Abstract: Neuronal activity and energy metabolism are tightly coupled processes. Previously, we found that nuclear respiratory factor 1 (NRF-1) transcriptionally co-regulates energy metabolism and neuronal activity by regulating all 13 subunits of the critical energy generating enzyme, cytochrome c oxidase (COX), as well as GluN1 (Grin1) and GluN2B (Grin2b) subunits of NMDA receptors. We also found that another transcription factor, nuclear respiratory factor 2 (NRF-2 or GA-binding protein) regulates all subunits of COX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…In agreement with our previous findings (26), the promoter of cytochrome c oxidase subunit 6b (COX6b) formed a specific DNA/NRF-2 shift and a DNA/NRF-2/NRF-2 antibody supershift complex when incubated with visual cortical nuclear extract (Fig. 3, lanes 1 and 3, respectively).…”
Section: In Vitro Binding Of Nrf-2 To the Promoter Of Bdnf Exon Ix-supporting
confidence: 79%
See 4 more Smart Citations
“…In agreement with our previous findings (26), the promoter of cytochrome c oxidase subunit 6b (COX6b) formed a specific DNA/NRF-2 shift and a DNA/NRF-2/NRF-2 antibody supershift complex when incubated with visual cortical nuclear extract (Fig. 3, lanes 1 and 3, respectively).…”
Section: In Vitro Binding Of Nrf-2 To the Promoter Of Bdnf Exon Ix-supporting
confidence: 79%
“…Our laboratory has shown that NRF-2 regulates all 10 nuclear-encoded and all three mitochondrial-encoded subunit genes of cytochrome c oxidase, an important energy generating enzyme in the mitochondria (25). Moreover, we found that NRF-2 links energy metabolism and neuronal activity at the transcriptional level by also regulating specific subunits of glutamatergic receptors (26,27). The present study adds a third component to this coupling, i.e.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations